2021
DOI: 10.1016/j.heliyon.2021.e06992
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of authentic leadership and employees' psychological capital on work engagement: evidence from Indonesia

Abstract: This study aims at investigating the positive effect of Authentic Leadership on Work Engagement and the mediating role of Psychological Capital (PsyCap). This study employed the Jobs Demands Resource (JD-R) model theory to explain the contribution of Authentic Leadership and PsyCap on Work Engagement. Also, the direct effect of Authentic Leadership on employees' PsyCap was examined. This study randomly selected participants from 1,120 employees in one of the largest public service offices in Indonesia. 192 emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 70 publications
6
33
0
3
Order By: Relevance
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
See 1 more Smart Citation
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
“…Numerous studies have confirmed that psychological capital and its interventions are related to reduced work-related problems, not to mention positive wellbeing and workrelated outcomes [96][97][98][99][100][101][102][103][104][105]. Research of the psychological capital in the public sector has evidenced its' numerous benefits [57,[106][107][108][109]. Similarly, the studies on psychological capital in the business, entrepreneurial, or marketing contexts demonstrated the added value of psychological capital and its interventions for the private sector organizations [110][111][112][113][114][115][116][117][118][119].…”
Section: Psychological Capitalmentioning
confidence: 99%
“…At the same time, FSSB adopted by supervisors can relieve anxiety, help employees resolve conflicts in the work and family field, and enhance the sense of belonging of employees ( Wang et al, 2020 ; Wang and Zhao, 2020 ). Niswaty et al (2021) also proved the connection between work-family needs, supervisor support and role satisfaction through a longitudinal study of the Chinese context.…”
Section: Introductionmentioning
confidence: 77%
“…In addition, domestic and foreign scholars have also explored the relationship between athlete engagement and athlete burnout. Scholars Guo et al (2021) and others found that athlete engagement has a predictive effect on athlete burnout, while scholars Samienia et al (2022) and others found that athlete burnout also predicts athlete engagement, meanwhile, psychological capital, psychological empowerment and psychological need have also been found in the fields of psychology and organizational management to be predictive of work engagement ( Amor et al, 2021 ; Niswaty et al, 2021 ; Liebenberg et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%